Pengaruh Desain Interior terhadap Minat Kunjung Pemustaka di Perpustakaan Tenas Effendy: The Effect of Interior Design on Visitor Interest in Tenas Effendy Library - Latiar, Hadira; Caesareani Fauzi, Sucy; H, Rosman (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study examines the influence of interior design on the interest of visiting library users in Tenas Effendy Library, a topic that is relevant to increasing library visits in public libraries. The purpose of this study was to determine whether the interior design of the library affects the interest of library visitors. This study used descriptive quantitative method, with data collection techniques through observation, questionnaires, and documentation. A total of 97 users were selected as samples through purposive sampling. Data analysis using T test and regression shows that there is a significant influence between interior design and interest in visiting the library, with a significance value of 0.00 <0.05, so that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. The R square value of 0.792 indicates that interior design has an effect of 79.2% on library patron interest, while the remaining 20.8% is influenced by other factors not observed in this study. The findings suggest that interior design has an important role in increasing library visits and has important implications for library space design.